Automação e otimização de processos: um estudo de caso em uma empresa de e-commerce na cidade de Mossoró-RN - Coimbra, Erik Kenes Silva (Universidade Federal Rural do Semi-Árido, 2020)
With the current competitive environment, organizations are increasingly looking for alternatives to differentiate themselves, through the optimization of their processes, to meet market demands. Thus, process management and automation tend to be essential tools in the organizational environment, as they make it possible to present significant improvements in processes. In this context, this research aimed to automate and optimize the process of shipping goods from an e-commerce store in the decoration segment, located in the city of Mossoró-RN, and specifically: mapping the process of shipping goods; identify harmful and limiting factors; eliminate or reduce limiting factors through automation, to decrease the total process time. The research is considered applied, quali-quantitative, exploratory and as a case study. A semi-structured interview was carried out to understand the shipping process and identify specific aspects that needed improvement, since, due to the large increase in the volume of sales, delays were being generated. To obtain an overview of the process, process mapping was performed. As a result, the limiting points of the process were identified and, in part, the automation was carried out, reducing the process time from 198 minutes to 13 minutes, maximizing the shipping capacity and reducing delays in the store's delivery logistics.
Keywords: Automação; Mapeamento de processos; E-commerce; Expedição; ENGENHARIAS::ENGENHARIA DE PRODUCAO